Allelic frequencies of 22 short tandem repeats loci and tri-allelic patterns of Penta D and TPOX identified in Gabonese population - Lendoye, Elisabeth; Mombo, Landry Erick; N’Negue ep. Mezui-Mbeng, Marie-Andree; Komba, Opheelia Makoyo; Ngoungou, Edgard Brice; Ovono Abessolo, Felix; Djoba Siawaya, Joel Fleury; Alt-Mörbe, Juliane (Scientific reports, 2023)
Short tandem repeats (STRs) are repeating DNA sequences used in forensic human identity testing and the diagnosis of aneuploidies. Many STRs like Penta D and TPOX are used routinely for paternity tests, but these tests are not widely used in sub-Saharan Africa. In this study we recruited individuals from Gabonese families seeking a paternity test. After DNA extraction from buccal swabs, we genotyped samples using a panel of 22 STRs. A total of 115 unrelated subjects from 39 families were included. Allele frequencies of the 22 STR loci were determined in unrelated Gabonese subjects. The most polymorphic loci were D21S11 (16 alleles) and FGA (17 alleles), while D3S1358 and TH01 loci were less polymorphic, with five alleles each. Deviation from Hardy–Weinberg equilibrium was observed for TPOX, D3S1358, CSFPO and D7S820 loci. We reported tri-allelic patterns that indicate aneuploidies at a combined frequency of 4% (4/115) with 3% for Penta D (1/35) and 3% for TPOX (3/102). Furthermore, we identified a new tri-allelic genotype 5-8-16 for the Penta D locus located on chromosome 21 in a healthy subject. In addition, we observed three tri-allelic variants of TPOX, located on chromosome 2, in healthy subjects, namely 8-10-11, 8-9-10, and 8-8-10. Our study revealed unsuspected polymorphic variations in Penta D and TPOX for the first time in Gabon, raising several questions about chromosomal disorders. Further population genetics studies are needed in Gabon to better characterize these variations, both qualitatively and quantitative.